A power reduction approach to green cloud computing (Research, Society and Development, 2023)
As cloud computing becomes increasingly prevalent in our daily lives and the business environment, it is essential that we are aware and proactive in managing the environmental impact of this technology. Green cloud computing is an approach that seeks to reduce energy consumption and CO2 emissions associated with cloud computing, while still providing the necessary functionality and performance. Through the use of simulators, such as CloudSim Plus, and the implementation of efficient algorithms for resource management, this study demonstrated that it is possible to achieve significant improvements in energy efficiency, reductions in operational costs, and a decrease in environmental impact without reducing computational capacity. An improvement of at least 49% in energy efficiency was observed, a reduction of at least 7% in direct costs, and a decrease of 50% in equivalent CO2 emissions. It is important to emphasize that these improvements were achieved without compromising the performance of the systems, as the processing times remained unchanged.